Tumoral Calcinosis as an Initial Complaint of Juvenile-Onset Amyopathic Dermatomyositis - Doh, Eun Jin (Ann Dermatol, 2016)
Calcinosis is rarely observed in juvenile-onset amyopathic dermatomyositis in contrast to juvenile-onset dermatomyositis. A 6-year-old female presented with several 0.5 to 2 cm-sized painless grouped masses on both knees for 3 years. The patient also presented with multiple erythematous scaly patches and plaques on both elbows, knuckles, buttock, ankles and cheeks. Her mother had similar skin lesions which were erythematous scaly patches on the knuckles and elbows, since her childhood. When skin biopsy was performed from a left knee nodule, liquid chalky discharge was observed. The biopsy results were consistent with calcinosis cutis. Other biopsies from erythematous patch of the patient and erythematous patch of her mother showed vacuolization of basal cell layer with inflammatory cell infiltrations. Laboratory findings showed normal range of serum phosphorus (4.5 mg/dl), calcium (9.3 mg/dl), 1,25-dihydroxy-vitamin D (10.8 ng/ml) and parathyroid hormone levels (11 pg/ml). Both patient and her mother had no history of muscle weakness and showed normal levels of muscle-specific enzyme. Both patients were diagnosed with juvenile-onset amyopathic dermatomyositis based on histopathology and cutaneous manifestations with no evidence of muscle weakness and no serum muscle enzyme abnormalities. Tumoral calcium deposits observed in daughter was diagnosed as dystrophic calcinosis which can be rarely seen in juvenile-onset amyopathic dermatomyositis. The patient is being treated with oral acetazolamide (40 mg/kg/d) for calcinosis.